Studies on Homalomeneae (Araceae) of Sumatera IV: Three new ornamental Homalomena (Chamaecladon clade) species - Boyce, P.C; Wong, Sin Yeng (Botanic Garden and Botanical Museum Berlin (BGBM), 2016)
Three new species of Homalomena (Chamaecladon clade) are described and illustrated from Sumatera (Sumatra), Indonesia